Reclassification of CTO crossing strategies in the ERCTO registry according to the CTO-ARC consensus recommendations - Vadalà Papale, Giuseppe; Mashayekhi, Kambis; Boukhris, Marouane; Behnes, Michael; Pyxaras, Stylianos; Christiansen, Evald Høj; Gutiérrez-Chico, Juan Luis; Maniscalco, Laura; Stojkovic, Sinisa; Bozinovic, Nenad Z.; Boudou, Nicolaus; Garbo, Roberto; et al. (JACC Cardiovascular interventions, 2024)
Background - The CTO-ARC (Chronic Total Occlusion Academic Research Consortium) recognized that a nonstandardized definition of chronic total occlusion (CTO) percutaneous coronary intervention approaches can bias the complications’ attribution to each crossing strategy. - Objectives - The study sought to describe the numbers, efficacy, and safety of each final CTO crossing strategy according to CTO-ARC recommendations. - Methods - In this cross-sectional study, data were retrieved from the European Registry of Chronic Total Occlusions between 2021 and 2022. - Results - Out of 8,673 patients, antegrade and retrograde approach were performed in 79.2% and 20.8% of cases, respectively. The antegrade approach included antegrade wiring and antegrade dissection and re-entry, both performed with or without retrograde contribution (antegrade wiring without retrograde contribution: n = 5,929 [68.4%]; antegrade wiring with retrograde contribution: n = 446 [5.1%]; antegrade dissection and re-entry without retrograde contribution: n = 353 [4.1%]; antegrade dissection and re-entry with retrograde contribution: n = 137 [1.6%]). The retrograde approach included retrograde wiring (n = 735 [8.4%]) and retrograde dissection and re-entry (n = 1,073 [12.4%]). Alternative antegrade crossing was associated with lower technical success (70% vs 86% vs 93.1%, respectively; P < 0.001) and higher complication rates (4.6% vs 2.9% vs 1%, respectively; P < 0.001) as compared with retrograde and true antegrade crossing. However, alternative antegrade crossing was applied mostly as a rescue strategy (96.1%). - Conclusions - The application of CTO-ARC definitions allowed the reclassification of 6.7% of procedures as alternative antegrade crossing with retrograde or antegrade contribution which showed higher MACCE and lower technical success rates, as compared with true antegrade and retrograde crossing.
Online verfügbar: 28. Oktober 2024, Artikelversion: 28. Oktober 2024
Gesehen am 26.03.2025